Correlation between the student’s perception about professional public accountant and the intention to pursue the career in auditing at the students of department of accounting STIE Binaniaga - Rizki Ahmad Fauzi (STIE Binaniaga, 2019)
This research aims to figure out the students’ perception about public accountant and their interest to be an auditor. Population of this research are the active students in the department of accounting at STIE Binaniaga year of 2016 (Semester 5) Sampling technique has applied Stratified Random Sampling and the quantity of the samples are 30 students after getting thru some sampling selection. Dependent variable is the students’ intention to work in auditing. And independent variabe is the students’ perception about professional accountant. The result of this research has indicated a significant correlation is occured between the students’ perception about public accountant and the students’ interest to pursue working in auditing. Keywords: Public Accountant, interest, students perception